MEMAKSIMALKAN PERMODALAN KOPERASI SEKOLAH - Alvi Izzatin Agnisia Putri; Zaskia Ardana; Tatiatun Khasanah; Haikal Akbar Nurdin; Siswadi (STKIP Subang, 2026)
School cooperatives play a strategic role as both economic institutions and learning media for students. However, many school cooperatives face challenges, particularly in terms of limited capital, which affects their sustainability and business development. This study aims to analyze strategies for maximizing school cooperative capital through a qualitative approach using library research. The data were collected from books, scientific journals, and relevant regulations related to cooperative management. The results show that optimizing capital is not only about increasing funds but also about implementing effective and integrated financial management strategies. Key strategies include strengthening internal capital through member participation, utilizing external funding selectively, applying transparent and accountable financial management, reinvesting profits, diversifying business activities, and adopting digital technology. These strategies can enhance operational efficiency, increase member trust, and improve the cooperative's competitiveness. Therefore, a comprehensive and sustainable approach is essential to ensure that school cooperatives become independent, professional, and competitive economic institutions in supporting educational activities.